Faktor-Faktor Yang Berhubungan Dengan Kepatuhan Penggunaan Apd Earplug Dan Sarung Tangan Pada Pekerja Unit Perbaikan Di PT. Kai Daop VI Yogyakarta Dipo Solo Balapan - Faniah, Aniek Masri, Dr. Suwaji, M. Kes (2016)
Law No. 1 of 1970 and Law No. 13 of 2003 of employment mandoted the company to implement the system K3 Occupational Healt and Safety such as the use of personal protective equipment at the workplace to prevent the risk of the inciden of accident and occupational disease. The purposes of the study was to determine the factors associated with aadjeremce ise earplug personal protective equiptment and gloves to workers repairt unit PT. KAI DAOP VI Yogyakarta Dipo Solo Balapan. This study used cross sectional design. The subjects o this study is 48 samples from 93 of the working population in the repair section PT. KAI Yogyakarta Regional Operational VI Dipo Solo Balapan. The available data is presented in the orm o frequency distributions and crosss tabulations wre analyzed by chi-square statsitic. The results showes that the workorce docile use earplug APD as mus as 25% and compliant use gloves personal protective equipment as much as 33.33% in the workplace. Statistical analysis showed that all factor have a significant relationship to compliance. The knowledge level o compliance significantly =0,030; 2=8.683 a significant atituted towards compliance =0,03;2=4.968, the avaibility of APD compliance =0,000; 2=13.395, comfort with compliance = =0,000;2=19.212 and training with obedience =0,001;2=11.679. suggestions based on research results to the company is providing and adequate number of protective equipment self, improve supervision of use personal protective equipment and give strict sancstions for non-complinace.